Clinical profile of patients presenting with heart failure with preserved ejection fraction - Palkhiwala, Neil B.; Patel, Rushin P.; Jani, Ruchi T.; Pandya, Jinal R.; Jani, Chinmay T.; Parikh, Ami P. (International Journal of Research in Medical Sciences, 2020)
Background: Evaluate the clinical profile of patients presenting with heart failure having normal or preserved ejection fraction and to determine the prevalence of comorbid illnesses in these patients. Methods: The study was carried out on patients that presented with heart failure at the Vadilal Sarabhai hospital, Ahmedabad between September 2014-2016. Heart failure patients with normal ejection fraction (>50%) were selected. Socio-demographic, vital signs, data of 2D Echocardiography and Tissue Doppler study were collected. The patients were classified as per the Echocardiographic study into four categories. Different laboratory parameters were compared in patients with respect to (a) grade of Hypertension (b), grade of anemia (c), HbA1c levels. Statistical analysis was done using the SPSS software v20. Mann-Whitney and Kruskal-Wallis tests were performed to compare the means between different study groups. Results: Out of the 70 patients, a majority (47%) belonged to the Grade 2 (pseudo-normalized) group of diastolic dysfunctions with most of them having only dyspnea and pedal edema (33%). 58.6% patients required intensive care for at least one day. Regarding co-morbidities 27 (38.6%) had hypertension, 34 (48.6%) were diabetic and 49(70%) had anemia. Patients with higher grade of dysfunction had higher HbA1c (p=0.023) and worsening anemia (p=0.003). Conclusions: Authors concluded that it is of prime importance to find, prevent and treat the comorbidities along with targeted therapies for HFpEF. Further evaluation can be done for clinical applicability of different markers including HbA1c and U.ACR for renal dysfunction in HFpEF.